Calcium mobilization from fish scales is mediated by parathyroid hormone related protein via the parathyroid hormone type 1 receptor - Rotllant, J. (2014)
The scales of bony fish represent a significant reservoir of calcium but little is known about their contribution, as well as of bone, to calcium balance and how calcium deposition and mobilization are regulated in calcified tissues. In the present study we report the action of parathyroid hormone-related protein (PTHrP) on calcium mobilization from sea bream (Sparus auratus) scales in an in vitro bioassay. Ligand binding studies of piscine 125I-(1 – 35tyr)PTHrP to the membrane fraction of isolated sea bream scales revealed the existence of a single PTH receptor (PTHR) type. RT-PCR of fish scale cDNA using specific primers for two receptor types found in teleosts, PTH1R, and PTH3R, showed expression only of PTH1R. The signalling mechanisms mediating binding of the N-terminal amino acid region of PTHrP were investigated. A synthetic peptide (10 8 M) based on the N-terminal 1 – 34 amino acid residues of Fugu rubripes PTHrP strongly stimulated cAMP synthesis and [3 H]myo-inositol incorporation in sea bream scales. However, peptides (10 8 M) with N-terminal deletions, such as (2 – 34), (3 – 34) and (7 – 34)PTHrP, were defective in stimulating cAMP production but stimulated [3 H]myo-inositol incorporation. (1 – 34)PTHrP induced significant osteoclastic activity in scale tissue as indicated by its stimulation of tartrate-resistant acid phosphatase. In contrast, (7 – 34)PTHrP failed to stimulate the activity of this enzyme. This activity could also be abolished by the adenylyl cyclase inhibitor SQ-22536, but not by the phospholipase C inhibitor U-73122. The results of the study indicate that one mechanism through which N-terminal (1 – 34)PTHrP stimulates osteoclastic activity of sea bream scales, is through PTH1R and via the cAMP/AC intracellular signalling pathway. It appears, therefore, that fish scales can act as calcium stores and that (1 – 34)PTHrP regulates calcium mobilization from them; it remains to be established if this mechanism contributes to calcium homeostasis in vivo.